Dataset for Measurement of thermal conductivity of epoxy resins during cure - Skordos, Alexandros A.; Struzziero, Giacomo; Remy, Berenice (Cranfield University, 2018)
- Thermal_conductivity_glycerine: Experimental and FE data of the thermal conductivity test run on glycerine at 100 degC and 4 degC. Includes also the sensitivity analysis of the measurement on thermocouple misplacement. - RTM6_cure_kinetics_results: Includes the isothermal and dynamic data for the RTM6 cure kinetics characterisation and the corresponding model. It also includes the sensitivity analysis on period and amplitude influence for RTM6 - 890RTM_cure_kinetics_results: Includes the isothermal and dynamic data for the 890RTM cure kinetics characterisation and the corresponding model. It also includes the sensitivity analysis on period and amplitude influence for 890RTM - XU3508_cure_kinetics_results: Includes the isothermal and dynamic data for the XU3508 cure kinetics characterisation and the corresponding model. - Di Benedetto_XU3508: Includes the dataused to build the Di Benedetto equation for the XU3508 resin system and the corresponding model - Cp_density_conductivity_data: Includes the Cp data and model, the density and the thermal conductivity data for the three resin systems under investigation: RTM6, 890RTM and XU3508 - Thermal_conductivity_model: Includes the data from the thermal conductivity tests for the three resin system and the fitting of the experimental data with the analytical model.
Keywords: 'epoxy'; 'cure'; 'thermal conductivity'; 'Composite and Hybrid Materials'; 'Polymers and Plastics'